DETERMINANTS OF GOOD CORPORATE GOVERNANCE, CAPITAL STRUCTURE AND ACCOUNTING CONSERVATISM IN INFLUENCING THE FINANCIAL PERFORMANCE OF IPO COMPANIES - Wibowo, Ilham Tejo; Ts, Kartika Hendra; Mursito, Bambang (Jurnal Ilmiah Global Education, 2023)
This study aims to examine and analyze the effect of GCG proxied in institutional ownership, managerial ownership, board of commissioners, independent commissioners, and audit committees, as well as capital structure and accounting conservatism on financial performance. This research uses a type of research with a quantitative approach with an ex post facto design. A sample of 44 companies going public in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) using the purposive sampling method. The data analysis method used in research is multiple regression for testing research hypotheses. The results showed that institutional ownership, independent commissioners, and audit committees had no significant effect on financial performance. Managerial ownership, the board of commissioners, capital structure, and accounting conservatism have a significant effect on financial performance. The combination of institutional ownership, managerial ownership, board of commissioners, independent commissioners, audit committee, capital structure, and accounting conservatism have a joint or simultaneous effect on the company's financial performance.